Myocardial deformation in athletes measured with feature tracking cardiovascular magnetic resonance. (3rd October 2022) - Silva, C; Marcos-Carrion, A; Garcia-Lopez, M P; Lopez-Lereu, M P; Monmeneu, J V; Higueras, L; Ferreira, A M; Maceira, A M
Abstract: Background: Morphological changes of the heart associated with exercise are well studied. However, changes in myocardial mechanics of athlete's heart are less understood. The aim of this study was to analyze myocardial deformation parameters in athletes and controls, using feature tracking cardiac magnetic resonance (FT-CMR). Methods: In a cohort of 73 athletes who had been submitted to CMR at 1.5T and 3 T (mean age 31±12 years, 69% males), we used CMR-FT to measure longitudinal, circumferential and radial strain and strain rates of both ventricles. Left ventricle (LV) longitudinal, circumferential and radial dyssynchrony index (L-SDI, C-SDI and R-CDI, respectively) was calculated as the standard deviation of the calculated time to peak strain percentages of the cardiac cycle with segmental strain analysis. We also measured these parameters in 73 age-matched healthy subjects. Results: In comparison to the control subjects, athletes revealed lower left and right ventricle global longitudinal strain (−14.24% vs. −13.31%, p=0.03, and −18.12% vs. −15.95% p=0.01, respectively) and right ventricular (RV) global radial strain (19.28 vs 15.74, p<0.05) – Figure 1. There were no significant differences in LV global radial and circumferential strain. LV longitudinal, radial and circumferential systolic strain rate were also lower in athletes compared to controls (−0.69 s –1 vs. −0.78 s –1, p=0.04; 1.35 s –1 vs. 1.50 s –1, p=0.03: −0.92 s –1 vs −0.98 s –1, p=0.05, respectively). Regarding LV dyssynchrony index, we found no significant difference for L-SDI (10.76% vs. 10.72%, p=0.956), but athletes group showed lower C-SDI and R-SDI values (5.99% vs 4.84%, p=0.006, and 5.53% vs 4.47%, p=0.002). Conclusion: Our study revealed attenuation of biventricular strain values and lower circumferential and radial LV dyssynchrony indexes in athletes, compared with healthy controls. We hypothesize that these differences may be related with exercise physiologic cardiac adaptations. Funding Acknowledgement: Type of funding sources: None.